Risk factors associated with arterial hypertension in patients with Systemic lupus erythematous. Holguín, Cuba - Raisa Rodríguez Hernández; Alberto Alberteris Rodríguez; Jackeline López Báster; Mariela Diéguez Martínez; Pedro Enrique Miguel-Soca; Yudelkis Cutié Anido (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: The presence of hypertension in patients with systemic lupus erythematous is a health problem that has not been studied in Holguín. Objective:To determine the cardiovascular risk factors associated with hypertension in patients with systemic lupus erythematous. Material and Methods: A cross-sectional study was conducted. The universe was composed of 193 patients with lupus who were treated in the Rheumatology consultation of the Clinical-Surgical Hospital of Holguín from March 3, 2014 to January 1, 2015.  The sample was made up of 81 patients who were randomly selected according to a 95 % confidence interval, a population size of 193, an estimated proportion of arterial hypertension of 0,20, a precision of a 7 %, and a design effect of 1.  The recommendations of the American College of Rheumatology were followed for the diagnosis of lupus erythematous, and national guidelines were used for the diagnosis of hypertension.  Clinical, anthropometric, and laboratory variables were determined.  Odds Ratio (OR), and 95 % (IC95%) confidence intervals for risk factors were determined. Results: The risk factors associated with hypertension in patients with lupus erythematous are: age (OR=1,04; IC95%:1,01-1,08), age of the lupus onset (OR=1,04; IC95%:1,01-1,08), diabetes mellitus (OR=8,50; IC95%:1,63-44,33), metabolic syndrome (OR=5,09; IC95%:1,87-13,84), hyperuricemia (OR=4,08; IC95%:1,07-15,44), and microalbuminuria (OR=19,81; IC95%:4,24-92,39). Conclusions:The patients with systemic lupus erythematous presented cardiovascular risk factors associated with hypertension, which are identifiable in the primary health care with variables of relatively easy realization.  Keywords:systemic lupus erythematous, metabolic syndrome, hypertension, risk factors, adults.